(untitled) (Cantho, 2013)
Contents: Food engineering at Massey University, Analysis and applications of milk fat globule membrane material, Sunflower oil supplemented with Schizophyllum commune extract: Its oxidative stability during accelerated storage,...
Keywords: Công nghiệp thực phẩm và thương mại,Food industry and trade; Kiểm soát chất lượng,Quality control